IMPLEMENTATION OF EU DIRECTIVES FOR CERTIFICATION OF THE STAFF IN THE SPA BUSINESS IN BULGARIA - Petya Kutincheva; Bistra Dimitrova (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Implemented was a psychometric experiment for survey the opinion of the leading experts from the 4 and 5 stars hotels and the first SPA certified MSc - SPA managers. The summarized results from the study highlight that the priorities are related to improve the quality of the services in the SPA business. We establish the acute need for increasing professional qualification of the personnel and harmonize the Bulgarian legislation with the EU directives. In this regard it is important to implement the national classificatory with new professions and unified for this purpose the theoretical categories: "Results of advanced training", "knowledge", "practical skills" and "competencies" in educational and qualification degree: "Bachelor", "MasterSc" and "PhD ".